Teologia Paulus Berdasarkan Kitab Titus - Dedi Bastanta (STT Injili Indonesia Medan, 2019)
Discussing of Paul’s theology means trying to understand the thoughts and cases of the church taked by Paul himself. It is thus very good to recite the Pauls’s letters to find the wealth of his theology. This article focuses on writing to Titus, especially regarding theological concepts. Paulss letter to Titus was studied exposition, although it emphasized the theological perspective of the New Testament.